Overlap in Sky Sport Football Debate: “Messi Vs Ronaldo – Is the Debate Finally Over?" - Hamid Abu Zayd, Nashr; Ruminda, Ruminda; Assiddiqi, Hasbi (Jurnal Pendidikan Indonesia, 2025)
One of the turn-taking infractions in discourse is overlapping. It happens when the following speaker interrupts the present speaker while they are still speaking, so denying them their turn. Although overlap is still a common occurrence and many speakers are ignorant of its forms and causes, this does not imply that it is always troublesome because, depending on the circumstances, it can sometimes be unproblematic. As a result, they have been unable to effectively employ overlap between those who and do not interrupt the discourse. Thus, this study’s goal is to classify the many types of overlap that are created and examine the reasons of overlap in the debate in the video "Messi VS Ronaldo - Is The Debate Finally Over?" Descriptive qualitative methodology was employed in this study, and documentation was the method of data collection. The primary theories that are employed are Schegloff’s (2000) categories of overlap and Wardhaugh’s (1985) explanations of overlap. The researcher discovered the kinds of overlap that took place and the underlying causes based on the data analysis of the dispute between the two football players. It is intended that this study would assist individuals in making appropriate use of overlap and avoiding overlap that might interfere with a interview